2017
DOI: 10.1111/jcpp.12721
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 of CATALISE: a multinational and multidisciplinary Delphi consensus study of problems with language development: Terminology

Abstract: BackgroundLack of agreement about criteria and terminology for children's language problems affects access to services as well as hindering research and practice. We report the second phase of a study using an online Delphi method to address these issues. In the first phase, we focused on criteria for language disorder. Here we consider terminology.MethodsThe Delphi method is an iterative process in which an initial set of statements is rated by a panel of experts, who then have the opportunity to view anonymi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
874
2
126

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,105 publications
(1,024 citation statements)
references
References 81 publications
22
874
2
126
Order By: Relevance
“…1997), which was formerly referred to as specific language impairment (SLI) (for a discussion of DSM‐5 classification and terminology, see Bishop et al . 2017). DLD can severely impact on children's mental health, and an increased risk for depressive symptoms is consistently reported in this group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1997), which was formerly referred to as specific language impairment (SLI) (for a discussion of DSM‐5 classification and terminology, see Bishop et al . 2017). DLD can severely impact on children's mental health, and an increased risk for depressive symptoms is consistently reported in this group.…”
Section: Introductionmentioning
confidence: 99%
“…Children with DLD experience problems in the content (semantics) and/or the form of language (phonology, morphology and syntax) (APA 2013, Bishop et al . 2017). Problems can occur in both receptive (e.g., understanding of word meanings or understanding the meaning of complex phrases) or expressive language (e.g., finding the right words to express ideas or production of grammatical sentences).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some commonly used terms include specific language impairment (SLI) or developmental language impairment (DLI). In the current study, the term developmental language disorder (DLD) is used as suggested in Bishop et al (2017). It refers to a profile of language difficulties that yields a barrier to effective functional communication (Reilly, Bishop, & Tomblin, 2014).…”
mentioning
confidence: 99%
“…There is still an insufficient number of qualified multilingual clinicians, and a lack of systematic diagnostic tools, as standardized tests are generally biased in favor of individuals from the majority culture. This especially accounts for multilingual children with suspected DLD as language difficulties are not associated with a known biomedical condition [13]. Since there is no robust normative data for the tremendously diverse population of multilingual children, there is a higher risk that language assessments may overidentify, but also underidentify, or misidentify multilingual children [14].…”
Section: Introductionmentioning
confidence: 99%